Spastic paraplegia preceding PSEN1-related familial Alzheimer's disease - Chelban, Viorica; Breza, Marianthi; Szaruga, Maria; Vandrovcova, Jana; Murphy, David; Lee, Chia-Ju; Alikhwan, Sondos; Bourinaris, Thomas; Vavougios, George; Ilyas, Muhammad; Halim, Sobia Ahsan; Al-Harrasi, Ahmed; et al. (Alzheimer's & Dementia : Diagnosis, Assessment & Disease Monitoring, 2021)
Introduction We investigated the frequency, neuropathology, and phenotypic characteristics of spastic paraplegia (SP) that precedes dementia in presenilin 1 (PSEN1) related familial Alzheimer's disease (AD).
CRIS-Team WoS Importer:2021-05-28